2005
DOI: 10.1016/j.orthres.2005.03.008.1100230621
|View full text |Cite
|
Sign up to set email alerts
|

Chondrogenic potential of progenitor cells derived from human bone marrow and adipose tissue: A patient-matched comparison

Abstract: Purpose: Stem cell-based tissue engineering represents a possible alternative for the repair of cartilage defects. Both bone marrow and adipose tissue contain pluripotential cells capable of chondrogenesis. This study was a qualitative and quantitative comparison of the chondrogenic potential of progenitor cells isolated from bone marrow aspirates and adipose tissue.Methods: Bone marrow aspirates (BM) and matching adipose tissue (AD) overlying the posterior superior iliac crest were obtained from patients unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(63 citation statements)
references
References 29 publications
(26 reference statements)
3
58
1
1
Order By: Relevance
“…[11][12][13][14] One study that compared chondrogenesis in ATMSCs and BMMSCs from the same individual reported that after 2 weeks of pellet culture, the amount of GAG and the expression of type II collagen mRNA was 120% and 500-to 5000-fold higher in BMMSCs than in ATMSCs. 11 Sakaguchi et al 12 showed that human bone marrow-or synoviumderived stem cells had greater chondrogenic and osteogenic potential than adipose tissue-derived stem cells. We also demonstrated that human ATMSCs have much weaker presentation as chondrogenic cells in both cell morphology and matrix production when cultured under the same chondrogenic conditions as BMMSCs.…”
mentioning
confidence: 99%
“…[11][12][13][14] One study that compared chondrogenesis in ATMSCs and BMMSCs from the same individual reported that after 2 weeks of pellet culture, the amount of GAG and the expression of type II collagen mRNA was 120% and 500-to 5000-fold higher in BMMSCs than in ATMSCs. 11 Sakaguchi et al 12 showed that human bone marrow-or synoviumderived stem cells had greater chondrogenic and osteogenic potential than adipose tissue-derived stem cells. We also demonstrated that human ATMSCs have much weaker presentation as chondrogenic cells in both cell morphology and matrix production when cultured under the same chondrogenic conditions as BMMSCs.…”
mentioning
confidence: 99%
“…A considerable number of papers have been published since 2003, addressing the question of which cell type, ASC or BMSC, possesses a higher chondrogenic potential (Table 1). A variety of authors concluded that BMSC can be more easily differentiated towards the chondrogenic lineage than ASC (Afizah et al, 2007;Danisovic et al, 2009;Huang et al, 2005;Im et al, 2005;Jakobsen et al, 2009;Kisiday et al, 2008;Koga et al, 2008;Liu et al, 2007;Vidal et al, 2008). However, Diekman et al (2010) pointed out that ASC and BMSC require unequal growth factor treatment for chondrogenic induction.…”
Section: The Potential Of Msc To Improve the State Of The Artmentioning
confidence: 99%
“…Regarding aggrecan expression, BMSC respond better to TGFβ, while ASC require BMP-6 (Jakobsen et al, 2009) Human In hyaluronic acid scaffolds chondrogenesis of BMSC was higher compared to ASC (Liu et al, 2007) Human BMSC differentiate better into osteoblasts and chondrocytes, while ASC have higher adipogenic differentiation potential (Afizah et al, 2007) Human BMSC and ASC from the same donor: BMSC are more suitable for cartilage tissue engineering than ASC (Huang et al, 2005) Human A patient-matched study: under the described conditions, BMSC demonstrated a higher chondrogenic potential (Im et al, 2005) Human Results of this study suggest that ASC have inferior capacity for chondrogenic differentiation (Winter et al, 2003) Human There are no differences in the expression of chondrogenic marker genes in 2D cultures between ASC and BMSC. In 3D cultures BMSC expressed a gene profile similar to that of osteoarthritic cartilage (Koga et al, 2008) Rabbit BMSC have higher chondrogenic potential compared to ASC in vitro and in vivo Rat There are no major differences between ASC and BMSC regarding the chondrogenic differentiation potential (Kisiday et al, 2008) Equine Superior chondrogenesis of BMSC was demonstrated in comparison to ASC (Vidal et al, 2008) Equine Superior chondrogenesis of BMSC was demonstrated in comparison to ASC Table 2.…”
Section: Referencementioning
confidence: 99%
“…Recent studies have suggested that adipose tissue and synovium may also be viable 388 GOLDRING sources of MSCs (24)(25)(26). However, procedures for obtaining MSCs from bone marrow and those other tissues are more invasive than muscle biopsies.…”
Section: Mary B Goldringmentioning
confidence: 99%